Safety of components and platforms of COVID-19 vaccines considered for use in pregnancy: A rapid review. Issue 40 (24th September 2021) - Ciapponi, Agustín; Bardach, Ariel; Mazzoni, Agustina; Alconada, Tomás; Anderson, Steven A.; Argento, Fernando J.; Ballivian, Jamile; Bok, Karin; Comandé, Daniel; Erbelding, Emily; Goucher, Erin; Kampmann, Beate; et al.
Highlights: Pregnant persons with COVID-19 may present with severe illness and adverse pregnancy or birth outcomes. Data about the safety of vaccination against COVID-19 for pregnant persons is limited. COVID-19 vaccines selected by COVAX showed no evidence of pregnancy-associated safety concerns. Pregnant persons may consider receiving these vaccines. Benefits could be higher for pregnant persons at high risk of exposure or with comorbidities. Abstract: Background: Rapid assessment of COVID-19 vaccine safety during pregnancy is urgently needed. Methods: We conducted a rapid systematic review, to evaluate the safety of COVID-19 vaccines selected by the COVID-19 Vaccines Global Access-Maternal Immunization Working Group in August 2020, including their components and their technological platforms used in other vaccines for pregnant persons. We searched literature databases, COVID-19 vaccine pregnancy registries, and explored reference lists from the inception date to February 2021 without language restriction. Pairs of reviewers independently selected studies through COVIDENCE, and performed the data extraction and the risk of bias assessment. Discrepancies were resolved by consensus. Registered on PROSPERO (CRD42021234185). Results: We retrieved 6757 records and 12 COVID-19 pregnancy registries from the search strategy; 38 clinical and non-clinical studies (involving 2, 398, 855 pregnant persons and 56 pregnant animals) were included. Most studies (89%) were conducted in high-income countries and were cohort studies (57%). Most studies (76%) compared vaccine exposures with no exposure during the three trimesters of pregnancy. The most frequent exposure was to AS03 adjuvant, in the context of A/H1N1 pandemic influenza vaccines, (n = 24) and aluminum-based adjuvants (n = 11). Only one study reported exposure to messenger RNA in lipid nanoparticles COVID-19 vaccines. Except for one preliminary report about A/H1N1 influenza vaccination (adjuvant AS03), corrected by the authors in a more thorough analysis, all studies concluded that there were no safety concerns. Conclusion: This rapid review found no evidence of pregnancy-associated safety concerns of COVID-19 vaccines or of their components or platforms when used in other vaccines. However, the need for further data on several vaccine platforms and components is warranted, given their novelty. Our findings support current WHO guidelines recommending that pregnant persons may consider receiving COVID-19 vaccines, particularly if they are at high risk of exposure or have comorbidities that enhance the risk of severe disease.